Late Jurassic (Upper Kimmeridgian) gastropods from Saal near Kelheim (Germany, Bavaria) - Joachim Gründel; Alexander Nützel (Zitteliana)
A new collection of Upper Jurassic (Kimmeridgian) gastropods from the reefal limestones of the Saal quarry near Kelheim (Lower Bavaria, Germany) is reported. It has yielded 119 species of which 80 species are nominate species, the others are treated in open nomenclature. This increases the number of known gastropod species from the Saal quarry by 54 (31 nominate species). A total of 178 gastropod species (107 nominate species) have now been reported from this locality making this occurrence the richest one from the Late Jurassic. Despite the fact that previously studied collections are from the same quarry and have the same age, these collections differ considerably from each other in species composition and relative abundances of shared species. This reflects facies differentiation in the quarry as well as colletion biases. One new genus (Kelheimia gen. nov.) and 15 new species are described: Scurriopsis cragolis sp. nov., Pseudorhytidopilus ? quadratus sp. nov., Rimulopsis danuviensis sp. nov., Nododelphinula oblonga sp. nov., Creniturbo gibbosus sp. nov., Kelheimia triangulata sp. nov., Neritopsis ? rotundatus sp. nov., Oonia kimmeridgiensis sp. nov., Eustoma ? gracilis sp. nov., Cryptoptyxis ? spinosus sp. nov., Turritella lucagrita sp. nov., Neuburgensia angulata sp. nov., Neuburgensia rara sp. nov., Diarthema aspera sp. nov., and Aphanoptyxis sinerugae sp. nov. Leptomaria tuberosa Gründel, Keupp & Lang, 2017 is seen as subjective synonym of Leptomaria goldfussi (Sieberer, 1907). Gymnocerithium ? convexoconcavum Gründel, Keupp & Lang, 2019 is placed in the genus Neuburgensia (comb. nov.). Amphitrochus ? gerberi Gründel, Keupp & Lang, 2017 is placed in the genus Serrettella (comb. nov.). Neritopsis subvaricosa Brösamlen, 1909 is placed in the genus Hayamiella (comb. nov.). Gymnocerithium ? convexoconcavum Gründel, Keupp & Lang, 2019 is placed in the genus Neuburgensia (comb. nov.). Nerinea tricincta Münster, 1844 is placed in the genus Aptyxiella (comb. nov.). Nerinea staszycii (Zeuschner, 1850) is placed in the genus Endoplocus (comb. nov.). Polyptyxisella clio (d’Orbigny, 1852) is placed in the genus Ptygamtis (comb. nov.).